Diesel particulate filter apparatus - KAWAMURA; HIDEO (1997)
This diesel particulate filter apparatus comprises a main filter, a sub-filter provided in a central portion of the main filter, and a bypass cylinder interposed between the main filter and sub-filter. A filter body constituting the main filter is made of long ceramic fiber, and the surface of the filter body is covered with a metal net, which is then fixed thereto. A heat resisting metal coil is provided on the surface of the filter body which is at the exhaust gas introducing side, and a ceramic fiber twisting is wound around and fixed to the filter body. A bypass valve adapted to be opened and closed by an actuator is provided on an exhaust gas introducing side of the sub-filter, and an admission port of the sub-filter is opened and closed by the bypass valve. Each wire rod constituting the metal net comprises a core member formed out of a material containing Ni and Cr and having a low resistance temperature coefficient and a large specific electric resistance value, and an intermediate member coating the core member and formed out of a material having a high resistance temperature coefficient and a small specific electric resistance value. The wire rod is covered with a corrosion resisting layer of coating of Al2O3 or ZrO2.